KONTRIBUSI KARAKTERISTIK ENTREPRENEURSHIP DAN IKLIM USAHA TERHADAP KEMAJUAN USAHA ( Studi pada Agroindustri Pangan pada Skala Usaha Kecil di Kediri) - Solichin, Endang (Jurnal Sosial Ekonomi Pertanian, 2010)
Research was designated to examine effects of entrepreneurship characteristic and enterprise climate on the business development, to test dominant factor that influencing enterprise progress of food agro-industries on small scale enterprise in Kediri.Questionnaire connects to 140 respondents of food agro-industrial companies of small scale enterprise in Kediri. Questionnaire seems to be engineered in Likert-scale by five selections, and then, analyzed by Structural Equation Modeling (SEM) technique provided with AMOS 4 software.The resultof research indicates that entrepreneurship characteristic imparts positive and purposively effect on enterprise progress. Enterprise climate also produces positive and sensibly effect on enterprise progress. Enterprise climate has more strong influence on enterprise progress than entrepreneurship characteristic. The findings result contributed to economic agriculture for especially agribusiness management.Withstanding of research judgment, triggering the growth and progress of food agro-industries on small scale enterprise in Kediri demands governmental intervention in shape of inventing beneficial enterprise climate through many government policies, that is accompanying and assistance as food agro-industries on small scale enterprise needed, minimize the unfavourable policies or does not support the small scale food agro-industries, support the market segment for the small scale food agro-industries, give support to the existence and development of small scale food agro-industries, give the entrepreneur training to increasing the entrepreneurship ability.Key words : Entrepreneurship, enterprise climate, Agro-industries